Spontaneous retrieval reveals right-ear advantage in prospective memory. Issue 4 (April 2018) - Rothen, Nicolas; Meier, Beat
The goal of this study was to investigate the impact of individual costs on prospective memory performance. Individual costs were assessed by contrasting participants with high costs and those with low costs. Specifically, we tested whether prospective memory performance is moderated by costs, cue-focality and intention specificity. Participants performed a dichotic listening paradigm where they had to indicate whether a word presented to one ear was abstract or concrete while ignoring the word presented to the other ear. For the prospective memory task, participants had to detect target items; half of them were presented focally to the same ear as the relevant words for the ongoing task and half of them were presented non-focally to the other ear. Moreover, half of the participants were given specific instructions and the other half were given categorical instructions. The results revealed a right-ear advantage for participants with low costs but not for participants with high costs. Moreover, the absence of costs was not necessarily accompanied by worse prospective memory performance. Given differential results under the same task conditions, we conclude that individual costs are an important factor which should be considered when investigating prospective memory processes.